2014
DOI: 10.1155/2014/240513
|View full text |Cite
|
Sign up to set email alerts
|

Age as a Prognostic Factor in Anaplastic Thyroid Cancer

Abstract: Background. Anaplastic thyroid cancer (ATC) is one of the tumors with the shortest survival in human medicine. Aim. The aim was to determine the importance of age in survival of patients with ATC. Material and Methods. We analyzed the data on 150 patients diagnosed with ATC in the period from 1995 to 2006. The Kaplan-Meier method and log-rank test were used to determine overall survival. Prognostic factors were identified by univariate and multivariate Cox regression analysis. Results. The youngest patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 19 publications
0
22
0
1
Order By: Relevance
“…In multiple retrospective studies analyzing disease course and aiming to identify prognostic factors for ATC, reported OS was highly variable ranging from few weeks to several years (Sugitani et al 2012, Sun et al 2013, Zivaljevic et al 2014. This implies that although ATC is fatal in most cases, risk stratification might be helpful.…”
Section: Prognostic Factors and Risk Stratificationmentioning
confidence: 99%
See 3 more Smart Citations
“…In multiple retrospective studies analyzing disease course and aiming to identify prognostic factors for ATC, reported OS was highly variable ranging from few weeks to several years (Sugitani et al 2012, Sun et al 2013, Zivaljevic et al 2014. This implies that although ATC is fatal in most cases, risk stratification might be helpful.…”
Section: Prognostic Factors and Risk Stratificationmentioning
confidence: 99%
“…Negative prognostic markers such as older age, initial distant metastatic disease, large primary tumor diameter (>5 cm) and elevated white blood count (WBC) have been described in several retrospective studies (Orita et al 2011, Sugitani et al 2012, Zivaljevic et al 2014.…”
Section: Prognostic Factors and Risk Stratificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Anaplastic thyroid cancer (ATC) is a rare but very aggressive type of cancer associated with a dismal prognosis (1)(2)(3)(4)(5)(6)(7). It represents only 1-5% of all thyroid tumours.…”
mentioning
confidence: 99%